Core‐Cone Structured Monodispersed Mesoporous Silica Nanoparticles with Ultra‐large Cavity for Protein Delivery. Issue 44 (1st October 2015) - Xu, Chun; Yu, Meihua; Noonan, Owen; Zhang, Jun; Song, Hao; Zhang, Hongwei; Lei, Chang; Niu, Yuting; Huang, Xiaodan; Yang, Yannan; Yu, Chengzhong
Abstract : A new type of monodispersed mesoporous silica nanoparticles with a core–cone structure (MSN‐CC) has been synthesized. The large cone‐shaped pores are formed by silica lamellae closely packed encircling a spherical core, showing a structure similar to the flower dahlia . MSN‐CC has a large pore size of 45 nm and a high pore volume of 2.59 cm 3 g −1 . MSN‐CC demonstrates a high loading capacity of large proteins and successfully delivers active β‐galactosidase into cells, showing their potential as efficient nanocarriers for the cellular delivery of proteins with large molecular weights. Abstract : Dahlia‐like silica : A new type of monodispersed mesoporous silica nanoparticle with core–cone structures (MSN‐CC) is synthesized. The cone‐shaped large pores are formed by silica lamellae closely packed encircling a spherical core, showing a structure similar to a dahlia. MSN‐CC demonstrates successful intracellular delivery of large protein of β‐galactosidase (β‐gal, 119 kDa) and retains its protein enzymatic activity.